Cultures of oral health
1 online resource (xiii, 246 pages)
Keywords: "Oral health is integral to well-being and quality of life. This important edited volume brings together leading scholars to address global oral health and the multiple ways in which theory, practice and discourse have shaped it in the modern period. Drawing on perspectives from dentistry, sociology, history and the wider humanities, this book will interest students and researchers of dentistry, public health, sociology of health and illness, the medical humanities and history"--